(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The modulation of aortic smooth muscle ion transport systems by active substances is a complex area within vascular physiology. The aorta, being the largest artery in the human body, plays a critical role in blood circulation and blood pressure regulation. The activity of ion transport systems in the smooth muscle cells of the aorta is pivotal for its contractility, vascular tone regulation, and overall cardiovascular function.